When Do Older Adults Become “Disabled”? Social and Health Antecedents of Perceived Disability in a Panel Study of the Oldest Old - KELLEY-MOORE, JESSICA A. (2006)
Disability carries negative social meaning, and little is known about when (or if), in the process of health decline, persons identify themselves as “disabled” We examine the social and health criteria that older adults use to subjectively rate their own disability status. Using a panel study of older adults (ages 72+), we estimate ordered probit and growth curve models of perceived disability over time. Total prevalent morbidity, functional limitations, and cognitive impairment are predictors of perceived disability. Cessation of driving and receipt of home health care also influence older adults’ perceptions of their own disability. A dense social network slowed the rate of labeling oneself disabled, while health anxiety accelerated the process over time, independent of health status. When considering perceived disability, the oldest old use multidimensional criteria capturing function, recent changes in health status and social networks, and anxiety about their health.